2011
DOI: 10.1590/s1415-47572011005000025
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidoses in northern Brazil: Targeted mutation screening and urinary glycosaminoglycan excretion in patients undergoing enzyme replacement therapy

Abstract: Mucopolysaccharidoses (MPS) are rare lysosomal disorders caused by the deficiency of specific lysosomal enzymes responsible for glycosaminoglycan (GAG) degradation. Enzyme Replacement Therapy (ERT) has been shown to reduce accumulation and urinary excretion of GAG, and to improve some of the patients’ clinical signs. We studied biochemical and molecular characteristics of nine MPS patients (two MPS I, four MPS II and three MPS VI) undergoing ERT in northern Brazil. The responsiveness of ERT was evaluated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…The reduction of GAG was of about 69% to 93%. This is in agreement with previous studies (Viana et al, 2011;Wraith et al, 2004;Wraith et al, 2007). One MPS patient had high GAG despite good clinical prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction of GAG was of about 69% to 93%. This is in agreement with previous studies (Viana et al, 2011;Wraith et al, 2004;Wraith et al, 2007). One MPS patient had high GAG despite good clinical prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies. 44,45,46 One MPS patient had high GAG despite good clinical prognosis. An earlier study also showed high GAG even after 6-year of ERT.…”
Section: Discussionmentioning
confidence: 99%
“…5 A Rede MPS Brasil, uma iniciativa criada para melhorar o diagnóstico e gestão destas doenças no Brasil, identificou, entre 2004 e 2006, 161 pacientes com MPS, entre os quais o tipo II mostrou maior prevalência (n=82) e o tipo VII o menor número de casos (n=4). 19 Estudos sugerem que as MPSs tipo II e VI sejam as mais frequentemente diagnosticadas no país, sendo desconhecidas as explicações para tal achado, e observada maior frequência no Sudeste seguida da região Nordeste. 1,2 No estudo de Villas-Boas et al, 20 de 2011, realizado no mesmo centro de referência do presente estudo, de 29 pacientes avaliados, 11 (38%) tinham diagnóstico de MPS tipo II, e o sexo masculino foi o mais prevalente, perfazendo 82,8% do grupo total.…”
Section: Discussionunclassified